Cartoon to solve teaching problem on mathematics - Yasin Gokbulut; Sultan Kus (International Journal of Evaluation and Research in Education (IJERE), 2019)
The aim of this study is to determine the effect of mathematics teaching with cartoons on the problem solving skills of primary school 2nd grade students based on addition and substraction. In the research, pretest-posttest control group design of the experimental model was used. In the classroom where the experimental group students were present, cartoon supported education was applied and the current program based teaching method was used in the control group class. The target population of the study consisted of 2nd grade students of all primary schools of the Ministry of National Education of Mersin. The population of the study consisted of 2nd grade students of all primary schools of the Ministry of National Education of Mersin. The study was conducted for 4 weeks in the fall semester of the 2015-2016 academic year. The experimental group consisted of 17 students and the control group consisted of 13 students. In order to determine the validity and reliability of the achievement test used in the study, item analysis was performed with the TAB program. The t-test was used to determine whether there was a significant difference between the pre-test and post-test scores of the groups. As a result of the research, it was observed that the success of the students in the problem solving in addition and substraction education has increased.